The Origin of Mitochondria and their Role in the Evolution of Life and Human Health - A. V. Panov (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
In studies of many medical and biological problems, there is a clear underestimation of the fundamental role of mitochondria in the evolution of eukaryotic organisms on the planet, including fungi, plants and fauna. It is  important to take into consideration numerous fundamental functions of mitochondria when studying the  human physiology and pathology, aging mechanisms. In this lecture, we briefly discuss the origin of mitochondria and their importance in the emergence of plants, which appeared on the planet 1–1.5 billion years later than eukaryotes with mitochondria, and served as the food basis for the rapid evolution of all species of the animal world. In the course of transformation of protobacteria into mitochondria, approximately 1000–1500 genes were transferred to the nucleus of eukaryotes, and the remaining 37 mitochondrial genes (mtDNA) exist in all types of animals. The presence of mitochondria in eukaryotes led to increased production  of reactive oxygen species and accelerated mutations in mtDNA. The spread of sexual reproduction may have been the way of protection against the accumulation of harmful mutations in mtDNA. At the same time, in all animal species mtDNA is inherited only maternally. In humans, the maternal inheritance of mtDNA led to uneven distribution, in small or inbred populations in particular, of a number of diseases with large prevalence in men, as well as male infertility, and in general accelerated aging and shorter lifespan in men, as compared with women. These negative consequences of the maternal inheritance of mtDNA were termed as “mother’s curse”. Recent studies have shown that mtDNA mutations are not the cause of human aging. The crisis of the mitochondrial free radical theory of aging is largely associated with the neglect of the protonated form of the superoxide radical, the perhydroxyl radical, which activates the peroxidation of polyunsaturated fatty acids in mitochondrial phospholipids. This results in production of various biologically active molecules and toxins. Therefore, initially aging may lack the manifestation of specific symptoms because of gradual accumulation of a wide variety of disorders and damages to the structure and functions of mitochondria and cells that finally lead to the development of diseases. The pathologies appear primarily in those organs that have a wide range of functional activity and a high dependence on oxygen consumption, namely the heart, brain, skeletal muscles and vascular epithelium.